Sound insulation of a novel laminated polymer matrix composite containing metallic hollow spheres based on phononic crystal structure design. (27th October 2021) - Yu, Tianmiao; Jiang, Fengchun; Cao, Mengxin; Wang, Chunhe; Qin, Ruonan; Guo, Chunhuan
Abstract: As a noval functional material designed and prepared artificially, one‐dimensional phononic crystal has a great prospect in the field of noise reduction. In this study, a novel one‐dimensional phononic crystal metamaterial based on the metallic hollow spheres (MHS)/polymer matrix laminated composites was designed and prepared. The result of impedance tube test shows that the laminated composite has excellent sound insulation performance. The incident direction of sound waves has little effect on the sound insulation performance of the laminated composites. The average sound insulation of MHSP/SR‐LC (MHSP side) was 44.4% higher than that of SR and 272.0% higher than that of PU. After analysis, it can be found that the average sound insulation of laminated composites increases with the acoustic impedance increasing, but the equivalent mass density and equivalent bulk modulus have little effect on it. The metallic hollow spheres can increase the sound energy loss by extending the transmission path of sound waves, andit can also improve the sound insulation by changing the density, elastic, and hardness of SR and PU matrix to increase the resonance strength of the spring‐mass oscillator. This work may open up new possibilities for the development of novel acoustic materials applied in noise control.